THE CRYSTAL STRUCTURE OF NA4(UO2) (CO3)3 AND ITS RELATIONSHIP TO SCHRöCKINGERITE - Li Y.; Krivovichev S.V.; Burns P.C. (My University, 2001)
Crystals of the compound Na4(UO2)(CO3)3 have been synthesized and the structure has been solved. It is trigonal with a= 9.3417(6), c = 12.824(1) Å, V = 969.2(1) Å3, space group Pc1 and Z = 4. The structure was refined on the basis of F 2 (wR2 = 4.2%) for all unique data collected using Mo-Kα X-radiation and a CCD-based detector. The final R1 was 2.0%, calculated for 534 unique observed (F o ≥ 4σ F ) reflections, and the goodness-of-fit (S) was 0.91. The structure contains a uranyl tricarbonate cluster composed of a uranyl hexagonal bipyramid that shares three equatorial edges with CO3 triangles. The uranyl tricarbonate clusters are connected through NaO6 and NaO5 polyhedra, forming a heteropolyhedral framework structure. This compound may be related to a uranyl carbonate phase with the same composition which has been reported as an alteration phase on the surface of Chernobyl ‘lava’, and as a mineral in the Jachymov ore district, Czech Republic.